Effects of social media usage : the well-being and flourishing of housewives - Norsiah Abdul Hamid; Sabrina Mohd Rashid; Mohd Sobhi Ishak; Wulan, Roro Retno (Penerbit Universiti Kebangsaan Malaysia, 2022)
Motives of social media usage vary and mostly depend on users’ background, interests, profession, and lifestyle. While the usage of social media has grown rapidly, it has caused numerous concerns. The literature on the motivations for women to use social media is edifying, but the results may not reveal the holistic continuum of social media usage motives among Malaysian housewives due to several distinctive and dynamic circumstances of this marginalised group. This study delves into housewives’ motives for social media usage and its effects on their well-being and flourishing based on the uses and gratification theory. Five motives have been proposed, namely escapism, information seeking, friendship maintenance, relationship initiation, and nostalgia, which were then tested for well-being and flourishing. In Study 1, a total of 268 housewives in Malaysia, who are active users of social media in their daily lives were involved in the survey. Data were analysed using SPSS v.23 and Partial Least Squares Structural Equation Modelling (PLS-SEM) using SmartPLS 3.1 applications. Meanwhile Study 2 was conducted by using focus group discussions with ten housewives. The findings of Study 1 revealed that motives of social media usage among housewives have a significant and positive impact on both well-being and flourishing. In contrast, Study 2 found five themes that emerged from the thematic analysis, strengthening relationships, emotional support, encouraging thoughts and characters, side income and support system, and acknowledgement of enrichment. This study provides insight into social media usage motives on women’s well-being and flourishing.